Do we worship the same God? Jews, Christians, and Muslims in dialogue - Volf, Miroslav (Grand Rapids, Mich. : William B. Eerdmans Pub. Co., 2012)
Often the differences between the three Abrahamic religions -- Judaism, Christianity, and Islam -- seem more obvious than their commonalities, leading to the question "Do we worship the same God?" Can the answer be "yes" without denying our differences? This volume brings Jewish, Christian, and Muslim philosophers and theologians together to answer this question, offering rare insight into how representatives of each religion view the other monotheistic faiths. Each of their contributions uniquely approaches the primary question from a philosophical perspective that is informed by the practice of worship and prayer. Concepts covered include "sameness" and "oneness," the nature of God, epistemology, and the Trinity. Do We Worship the Same God? models serious-minded, honest, and respectful interreligious dialogue and gives us new ways to address an ongoing question.
The same God? : the perspective of faith, the identity of God, tolerance, and dialogue / Christoph Schwöbel -- Christians, Muslims, and the name of God : who owns it, and how would we know? / Denys Turner -- The same God? / Amy Plantinga Pauw -- God between Christians and Jews : is it the same God? / Alon Goshen-Gottstein -- Do Muslims and Christians believe in the same God? / Reza Shah-Kazemi -- Do we worship the same God? / Peter Ochs.
Includes bibliographical references.
Description based on print version record.
Keywords: God; Abrahamic religions; Religions -- Relations; Judaism; Christianity; Islam; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; Electronic books